Development and characterization of chitosan-based edible coating incorporated with Curcuma longa (turmeric) essential oil: article / Mohamad Khairul Azwanizam Baharuddin, Norasmah Mohamed Manshor and Noorsuhana Mohd Yusof - Baharuddin, Mohamad Khairul Azwanizam; Mohamed Manshor, Norasmah; Mohd Yusof, Noorsuhana (2017)
Common problems related with fruits and vegetables such as foodborne pathogens that can cause foodborne illnesses, precocious decaying and economic losses related with fresh fruits retention have led to the development to find a technologies and systems for the main reason to protect the fruits and vegetables. One of the advance technology used nowadays is edible coatings based on natural compound. In this research, chitosan which is most widely used natural compounds in the edible coating development have been chosen. This paper provides a review on the effects of main edible coating components, chitosan (100 ml), turmeric essential oil (0, 5, 10, 15, 20 µl) and starch (4g, 6g, 8g Tapioca powder) on the analysis of appearance, color, texture and surface tension of coated strawberry were studied during 5 days of storage at room temperature (26˚C±2˚C) and 50-60% relative humidity. Results showed that all the analysis give the same results which is addition of 20 µl of turmeric oil and 6g of tapioca powder into the chitosan solution possible to extend the shelf-life of strawberry except for the surface tension analysis which is addition of 5, 10 and 15 µl of turmeric oil and 6g of tapioca powder give a good results for surface tension values.